Taxation of Historical and Artistic Real Estate - Maria Pia Nastri (Prawo Budżetowe Państwa i Samorządu)
The article presents general aspects of the taxation of historical and artistic real estate. It includes a few kinds of taxes. Firstly an income tax derived from ownership of properties of historical and artistic interest is discussed. Secondly, a group of indirect taxes and levies should be taken into account. There are inheritance tax and donation tax as well as local taxes known as IMU, TASI and TARSU.